ANALYSIS OF WATER QUALITY IN SUPPORTING MANGROVE ECOSYSTEM REHABILITATION ON THE BULAKBARU COAST, JEPARA - Desti Setiyowati; Arif Mustofa; Nurcahyo Kursistiyanto (Jurnal Disprotek, 2026)
Mangrove ecosystems play an essential role in maintaining the stability of coastal environments; however, mangrove conditions along the Bulakbaru coast, Jepara, have been increasingly pressured by coastal abrasion and human activities. The success of mangrove rehabilitation efforts is strongly influenced by surrounding water quality conditions. This study aimed to evaluate water quality as a supporting basis for mangrove ecosystem rehabilitation in the Bulakbaru coastal area, Jepara. The research was conducted in August 2024 by establishing three observation stations selected using a purposive sampling method. Water quality parameters analyzed included temperature, salinity, pH, dissolved oxygen (DO), ammonia (NH₃), nitrate (NO₃⁻), phosphate (PO₄³⁻), and total suspended solids (TSS). Physicochemical parameters were measured in situ and through laboratory analysis, and the results were subsequently compared with marine water quality standards for biota based on the Decree of the Minister of Environment No. 51 of 2004. The results indicated that temperature, salinity, pH, phosphate, and ammonia generally remained within the established quality standards. Dissolved oxygen concentrations exhibited spatial variation, with low values observed at Station II, indicating environmental stress associated with high organic loads and limited water circulation. Furthermore, nitrate concentrations at all observation stations exceeded the permissible threshold, while relatively high TSS values reflected strong influences from terrestrial activities. Overall, the water quality conditions of the Bulakbaru coastal waters still have the potential to support mangrove rehabilitation; however, sustainable management of nutrient and organic matter inputs from land is required.   ANALISIS KUALITAS AIR DALAM MENDUKUNG REHABILITASI EKOSISTEM MANGROVE DI PESISIR BULAKBARU, JEPARA Ekosistem mangrove memiliki peran penting dalam menjaga keseimbangan ekosistem pesisir, namun keberadaannya di pesisir Bulakbaru, Jepara, mengalami tekanan akibat abrasi dan aktivitas antropogenik. Keberhasilan rehabilitasi mangrove sangat dipengaruhi oleh kondisi kualitas perairan. Penelitian ini bertujuan untuk menganalisis kualitas air sebagai dasar pendukung rehabilitasi ekosistem mangrove di pesisir Bulakbaru, Jepara. Penelitian dilaksanakan pada bulan Agustus 2024 dengan menetapkan tiga stasiun pengamatan menggunakan metode purposive sampling. Parameter kualitas air yang dianalisis meliputi suhu, salinitas, pH, oksigen terlarut (DO), amonia (NH₃), nitrat (NO₃⁻), fosfat (PO₄³⁻), dan total padatan tersuspensi (TSS). Pengukuran parameter fisika-kimia dilakukan secara in situ dan analisis laboratorium, kemudian dibandingkan dengan baku mutu air laut untuk biota berdasarkan Keputusan Menteri Lingkungan Hidup No. 51 Tahun 2004. Hasil penelitian menunjukkan bahwa suhu, salinitas, pH, fosfat, dan amonia umumnya masih berada dalam kisaran baku mutu. Nilai DO menunjukkan variasi antar stasiun, dengan kondisi rendah pada Stasiun II yang mengindikasikan adanya tekanan lingkungan akibat beban organik dan sirkulasi air yang kurang optimal. Konsentrasi nitrat di seluruh stasiun telah melampaui baku mutu, sedangkan nilai TSS relatif tinggi yang mencerminkan kuatnya pengaruh aktivitas daratan. Secara keseluruhan, kualitas perairan pesisir Bulakbaru masih berpotensi mendukung rehabilitasi mangrove, namun diperlukan pengelolaan input nutrien dan bahan organik dari daratan secara berkelanjutan.